2017
DOI: 10.1186/s12978-017-0307-4
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum intentions on contraception use and method choice among breastfeeding women attending a university hospital in Ohio: a cross-sectional study

Abstract: BackgroundFew postpartum women use effective contraception and those who use less effective methods have increased rates of unintended pregnancy. Little is known about postpartum contraception intentions among breastfeeding women. Our objectives were to measure the extent of prenatal contraceptive counseling, to assess contraceptive intentions, and to identify correlates of both among postpartum women who were planning to breastfeed.MethodsWe conducted a cross-sectional study using a convenience sample of 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 20 publications
3
16
2
Order By: Relevance
“…In the present study, the most preferred modern contraceptives intended to use by study participants were implants (43%) and injectables 16%. The result was in line with the studies done in America [ 27 ] revealing that 38% and 12% of postpartum women preferred to use implants and injectables, respectively. There were also 19.2% of postpartum women who preferred to use implants whereas 18.4% of postpartum women intend to use injectables in Nigeria [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the most preferred modern contraceptives intended to use by study participants were implants (43%) and injectables 16%. The result was in line with the studies done in America [ 27 ] revealing that 38% and 12% of postpartum women preferred to use implants and injectables, respectively. There were also 19.2% of postpartum women who preferred to use implants whereas 18.4% of postpartum women intend to use injectables in Nigeria [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this study the prevalence of intention to use on modern contraceptive among postpartum women was 84.3%. This result was slightly lower than the finding in United State of America which reported [90%] [ 9 ]. This variation could be explained by the difference of study setting, accesses to information and availability to services use.…”
Section: Discussioncontrasting
confidence: 75%
“…The tool was prepared originally in English and translated to local language ( Tigrigna ) and translated back to English in order to maintain internal consistency. The tools was adopted from similar studies [ 9 , 10 ], but customized for this study. The questionnaire included sections on socio demographic characteristics of respondents, their maternal health service use, their reproductive intentions, their knowledge and current adoption and their intentions to use contraceptive methods among postpartum women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to the fact that implant is not user dependent and may not easily seen by partners [11,25]. This may again partly explain the partners' influence over the women's contraceptive choice [26,27]. Our finding is in contrast with studies in Uganda and Malawi which showed injectable was the most preferable contraceptive [4,21,28].…”
Section: Plos Onementioning
confidence: 60%